ANALISIS FINANCIAL DISTRESS PADA INDUSTRI KOSMETIK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) UNTUK MEMPREDIKSI POTENSI KEBANGKRUTAN PERUSAHAAN - Halimatusyakdiah Halimatusyakdiah; Abu Kosim; Eka Meirawati (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
This study aims to analyze the potential bankruptcy of companies in the cosmetic industry listed in Indonesia Stock Exchange (IDX) 2011-2013. One indicator of the company has a good performance can be seen from the financial aspects. Financial distress are close to bankruptcy stage marked by uncertainty about profitability in the future. Companies experiencing financial distress in the long term have a tendency to bankruptcy. Therefore, it is necessary bankruptcy prediction model that can provide early warning for the company. This study uses three bankruptcy prediction model, namely Springate, Zmijewski, and Grover. The results of this study indicate that the financial performance of the Cosmetics Industry analyzed with Springate Method namely PT Martino Berto Tbk, PT Unilever Indonesia Tbk, PT Mandom Indonesia Tbk classified in a healthy condition of the company for 2011-2013. While PT Mustika Ratu Tbk classified in healthy condition in 2011-2012 and classified in poor condition in 2013. Zmijewski Model Analysis (X-Score) at the Cosmetic Industry showed that there are only 2 companies are classified in a healthy condition, namely PT Mandom Indonesia Tbk , and PT Mustika Ratu Tbk in 2011 and 2012, while the others are in a vulnerable condition and bad. Grover Model Analysis (G-Score) at the Cosmetic Industry listed in Indonesia Stock Exchange (IDX) 2011-2013 showed that all companies included in the cosmetics industry are classified in a good health or not potentially banckrupt of the company.This study aims to analyze the potential bankruptcy of companies in the cosmetic industry listed in Indonesia Stock Exchange (IDX) 2011-2013. One indicator of the company has a good performance can be seen from the financial aspects. Financial distress are close to bankruptcy stage marked by uncertainty about profitability in the future. Companies experiencing financial distress in the long term have a tendency to bankruptcy. Therefore, it is necessary bankruptcy prediction model that can provide early warning for the company. This study uses three bankruptcy prediction model, namely Springate, Zmijewski, and Grover. The results of this study indicate that the financial performance of the Cosmetics Industry analyzed with Springate Method namely PT Martino Berto Tbk, PT Unilever Indonesia Tbk, PT Mandom Indonesia Tbk classified in a healthy condition of the company for 2011-2013. While PT Mustika Ratu Tbk classified in healthy condition in 2011-2012 and classified in poor condition in 2013. Zmijewski Model Analysis (X-Score) at the Cosmetic Industry showed that there are only 2 companies are classified in a healthy condition, namely PT Mandom Indonesia Tbk , and PT Mustika Ratu Tbk in 2011 and 2012, while the others are in a vulnerable condition and bad. Grover Model Analysis (G-Score) at the Cosmetic Industry listed in Indonesia Stock Exchange (IDX) 2011-2013 showed that all companies included in the cosmetics industry are classified in a good health or not potentially banckrupt of the company.